Simple Fabrication of Hydrophobicity-Controlled Fe-ZSM-5 for Aqueous-Phase Partial Oxidation of Methane with Hydrogen Peroxide - Hwang, Seok Young; Kwon, Minjae; Hwang, Jongkook; Park, Eun Duck (Catalysts, 2024)
Surface hydrophobicity is an important factor in controlling the catalytic activity of heterogeneous catalysts in various reactions, particularly liquid-phase reactions using water as the (co)solvent. In this study, the surface hydrophobicity of Fe-ZSM-5 was successfully controlled using a simple coating method in which furfuryl alcohol was used as the carbon precursor. Various techniques, such as N2 physisorption, temperature-programmed desorption of ammonia, and contact angle measurements of water droplets, were used to characterize the catalysts. Fe-ZSM-5 catalysts with different degrees of hydrophobicity were used for the aqueous-phase selective oxidation of methane with H2O2. The positive effect of the surface carbon coating on the catalytic performance was confirmed when the carbon content was not sufficiently high to block the pores.
Keywords: aqueous-phase oxidation; Fe-ZSM-5; hydrogen peroxide; hydrophobicity; methane